Dissociating the Disruptive Effects of Irrelevant Music and Speech on Serial Recall of Tonal and Verbal Sequences - Kattner, Florian; Meinhardt, Hanna (Frontiers in Psychology, 2020)
Task-irrelevant speech or music sounds are known to disrupt verbal short-term memory even when participants are instructed to ignore the sound, suggesting that automatically processed acoustical changes interfere with the rehearsal of phonological items. However, much less is known about auditory distraction in tasks that require the memorization and recall of non-phonological auditory items. In the present study, both musically trained and untrained participants were asked to memorize random tone sequences (consisting of low, medium, and high pitch tones) while task-irrelevant sound was presented. Irrelevant instrumental music was found to produce more disruption of tonal recall than white noise, whereas irrelevant speech produced intermediate levels of disruption. In contrast, only speech produced significant interference in an analogous verbal recall task. Crucially, although musically trained participants were able to recall more tones in general, the degree of auditory distraction that was produced by irrelevant music in the tonal recall task was found to be independent of musical expertise. The findings are in line with the assumption of two separate mechanisms for the maintenance of tonal and phonological information. Specifically, short-term memory for tone sequences may rely on a pitch-based rehearsal system which is disrupted by the perception of irrelevant pitch changes as contained in instrumental music (and to a lesser extent in speech), whereas serial recall of verbal items is most sensitive to phonological sounds.